1998
DOI: 10.1084/jem.188.10.1795
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated Protein Kinase Kinase Antagonized Fas-associated Death Domain Protein–mediated Apoptosis by Induced FLICE-inhibitory Protein Expression

Abstract: Fas and Fas-associated death domain (FADD) play a critical role in the homeostasis of different cell types. The regulation of Fas and FADD-mediated cell death is pivotal to many physiological functions. The activation of T lymphocytes by concanavalin A (Con A) inhibited Fas-mediated cell death. We identified that among the several activation signals downstream of Con A stimulation, mitogen-activated protein (MAP) kinase kinase (MKK) was the major kinase pathway that antagonized Fas-triggered cell death. MKK1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 48 publications
(72 reference statements)
7
87
2
Order By: Relevance
“…30 However, more recent results show no correlation between FLIP expression and resistance to TRAIL in these tumor cells. 78 Although MAPK stimulation in Jurkat T cells with concanavalin A has recently been reported to induce FLIP, 54 we however have found no changes in FLIP (L/S) or IAPs mRNA expression when Jurkat cells are treated with PDBu. These results support our data with CHX in which we show that the PDBu-mediated inhibitory action is protein synthesisindependent.…”
Section: Cell Death and Differentiationcontrasting
confidence: 50%
“…30 However, more recent results show no correlation between FLIP expression and resistance to TRAIL in these tumor cells. 78 Although MAPK stimulation in Jurkat T cells with concanavalin A has recently been reported to induce FLIP, 54 we however have found no changes in FLIP (L/S) or IAPs mRNA expression when Jurkat cells are treated with PDBu. These results support our data with CHX in which we show that the PDBu-mediated inhibitory action is protein synthesisindependent.…”
Section: Cell Death and Differentiationcontrasting
confidence: 50%
“…30 Furthermore, it has been reported that Bcl-2 expression is upregulated by Erk 31 and that the MAPK pathway could antagonize death receptor-mediated apoptosis by inducing FLICE-inhibitory protein (cFLIP) expression. 32 However, our results indicate that the apoptosis antagonizing effect of a PKC/MAPK activator does not require de novo protein synthesis. Several authors have shown that MAPK pathway protects from apoptosis triggered by different stimuli at the level of mitochondria.…”
Section: Discussionmentioning
confidence: 61%
“…32 Its ability to increase the expression of the FLICElike inhibitory protein FLIP suppresses sensitivity towards FasL-mediated apoptosis by preventing caspase 8 activation independently of PKB signaling. 33 The relative importance of ERK1/2 and ERK5 in mediating cell survival is likely to be stimulus-and cell type-specific. For example, whereas ERK1/ 2 and ERK5 are both required for mediating neuronal survival in response to NGF, 34 ERK5 is critical for the survival of endothelial cells during development.…”
Section: Discussionmentioning
confidence: 99%